Effectiveness and Tolerability of Trimetazidine 80 mg Once Daily in Patients with Chronic Coronary Syndrome in Brazil: The V-GOOD Observational Study - Luís Henrique Wolff Gowdak; Paulo Magno Martins Dourado; Dalton Bertolim Précoma; César de Oliviera Lopes Dusilek; Francisco Maia da Silva; Juan Carlos Yugar-Toledo; Felipe Montes Pena; Domingos Antônio de Almeida Gomes; Elizabeth do Espírito Santo Cestário; Olavo Raimundo Guimarães; Conrado Roberto Hoffmann Filho; Carlos Filinto de Almeida; et al. (Cardiology and Therapy)
Abstract Introduction The V-GOOD study evaluated the effectiveness of trimetazidine modified-release (MR) 80 mg once daily (OD) in patients with chronic coronary syndrome (CCS) who remained symptomatic despite antianginal therapies in routine clinical practice. Methods This prospective, observational study involved 1026 adult outpatients with symptomatic CCS from 70 sites in Brazil who were prescribed trimetazidine MR 80 mg OD plus background antianginal treatment. Data on number of angina attacks, short-acting nitrate consumption, prevalence of angina-free patients, severity of angina, patient-reported daily physical activity impairment, treatment adherence, tolerability, and cardiologist and patient satisfaction were collected at baseline (V1), then at 1 month (V2) and 3 months (V3). Results Following the addition of trimetazidine MR 80 mg OD, the mean ± standard deviation number of angina attacks per week decreased from 3.1 ± 2.8 at V1 to 1.0 ± 2.1 at V2, and 0.7 ± 1.7 at V3, with concurrent reductions in short-acting nitrate consumption, patient-reported daily physical activity impairment and the proportion of patients with limiting angina (Canadian Cardiovascular Society class III or IV), and increases in the proportion of angina-free patients (all p < 0.001 vs. V1). Most cardiologists rated trimetazidine MR 80 mg OD as satisfactory/very satisfactory (90.7% for effectiveness and 94.8% for tolerability); most patients rated the treatment schedule as convenient/very convenient (97.2%) and satisfactory/very satisfactory (97.1%). Treatment was well tolerated. Conclusions These data support the symptomatic benefits and good tolerability associated with adding trimetazidine MR 80 mg OD to other antianginal therapies in patients with persistent symptoms. Graphical abstract available for this article. Trial registration number NCT06464276. Graphical Abstract